KISRUH PILKADA LANGSUNG GUGAT-MENGGUGAT PASCA HASILPENGHITUNGAN SUARA PADA PILKADA SERENTAK 2015 - Askarial, Askarial (Aksara Public, 2017)
The author conducted this study with the title Kisru sue-sue Direct Election Post-Election Vote Count Results In Unison 2015 objective of this study to describe and know the results kisru immediately after the counting of votes in the elections in 2015. This research method is descriptive method qualitave. The attitude of the elite, especially the pairs of candidates must prioritize politeness, politicking in a healthy, cultivate the attitude of accepting defeat, the maturation of politics. Each competition will be there to win it. Therefore, in order to avoid mutual suspicion and feeling cheated, then the implementation of the election by the organizers to be really fair that organizers had to work optimally, the monitoring function should also be run firm, thus reducing fonomena sue suing Constitutional Court, because has been the implementation of fair local elections.